THE VALUATION OF ECOSYSTEM CULTURAL SERVICES IN GEP ACCOUNTING: A CASE OF KHOVD PROVINCE - Gaanjuur, Gerelsuren (Journal of Business and Innovation (Бизнес & Инноваци), 2025)
Ecosystem economic valuation is an effective way to measure and understand the significance of the benefits people receive from ecosystems. The Gross Ecosystem Product (GEP) concept seeks to employ specific indicators for quantifying the economic value of all ecosystem products and services. GEP is the total value of final ecosystem goods and services supplied to human wellbeing in a region annually. It can be measured in terms of biophysical value and monetary value. This study aimed to examine the usage of the travel cost method in Mongolia for the first time and introduced new knowledge for ecosystem valuation. The GEP was calculated at the provincial level, and a framework was customized for the unique economic and ecological situations of Khovd province. The findings revealed that the total GEP in Khovd province ranged from 110040.7 million dollars to 113650.2 million dollars in 2015 and 2020, respectively. Among the different components of GEP, the value of ecosystem cultural services shared a tiny proportion, accounting for 0.00356% and 0.0033% in both 2015 and 2020.